Descodificar as paredes da cidade: da crítica à gentrificação ao direito da habitação no Porto - Barbosa, Inês; Lopes, João Teixeira (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2020)
In Porto the intensification of touristification goes hand in hand with gentrification, reorganizing, at a breakneck pace, the social composition of the city. This article is the result of an autonomous research, framed in visual sociology and sociology of walking. “Walking” is assumed here as a form of immersion, exploration and decoding of the city. In nine months, we collected a hundred visual displays, scattered throughout the territory. The gathered images translate a polyphonic discourse, underlying several agents, receivers and demands. Although all of them express a common critique regarding the direction that the city has been taking in the urban, social and political aspects.